Thermophysical properties of dimethyl ether/Athabasca bitumen system. (21st September 2017) - Haddadnia, Ali; Azinfar, Bahareh; Zirrahi, Mohsen; Hassanzadeh, Hassan; Abedi, Jalal
Abstract : Solvent‐aided thermal recovery processes have recently gained practical and research interests among other thermal recovery methods due to their reduced environmental footprint and superior energy efficiency. One of the main challenges in design of solvent‐based methods is selection of an appropriate solvent that maximizes the bitumen and solvent recoveries. This study attempts to introduce dimethyl ether (DME) as a non‐conventional solvent for heavy oil and bitumen recovery. To investigate the performance of the proposed solvent, thermophysical properties of DME/bitumen are studied. Vapour‐liquid equilibrium measurements including solubility, density, and viscosity are performed at three temperatures (100, 125, and 150 °C) and pressures up to 6 MPa. The results were compared with propane/bitumen and butane/bitumen systems. All the measured properties fall between propane and butane systems. The solubility and density data were fairly represented using PR‐EoS with AARDs of 10.3 and 1.43 %, respectively, and viscosity data were correlated applying the Pederson corresponding state model with an AARD of 10.7 %. The results suggest that DME is a suitable substitute for solvents such as propane and butane in solvent‐aided thermal recovery of bitumen from oil sands.